The The Effects of Tax Avoidance on Firm Value - Serly, Serly; Yuliani, Nova (Global Financial Accounting Journal, 2024)
Purpose - The main objective of this study is to determine the effect of tax avoidance on firm value. Company size, leverage, ROA, ROE and Sales Growth are control variables. A quantitative approach method is used for this research, where the results of the research were statistically processed based on data originating from the input process, collection process and analysis process. Research Method - A purposive sampling was taken for data collection stage, which samples of this study namely company listed on the Indonesia Stock Exchange for the period of 2016 to 2020. The collected samples are then processed to find out whether there is a connection between one and another. There are 220 companies that fulfill the sample criteria in this research. Findings - The outcome of this study explain that firm value is not affected by tax avoidance, firm size has a significant negative effect on firm value, while ROA and leverage have significant positif effect on firm value, meanwhile ROE has no significant effect on firm value, leverage has a significant positive effect on firm value, as well sales growth. Implication - Research on the effect of tax avoidance on firm value generally shows that tax avoidance can increase firm value in the short term through tax cost savings. However, the research results found that there was no influence between tax avoidance and firm value. The implication is that tax avoidance practices are not considered significant by investors in assessing firm value. This suggests that other factors, such as operational performance or market conditions, may play a greater role in determining firm value, and tax avoidance does not always provide significant benefits or losses.